Implementasi Strategi Kooperatif Tipe Number Heads Together (NHT) pada Mata Pelajaran Pendidikan Agama Islam (PAI) di SMKN 1 Padang Panjang - Anggi Sari Putri; Asneli Asneli (Kampus Akademik Publiser, 2023)
During the learning process, there are still students who do not follow the rules of learning, such as during discussions where they should be able to work together and be cohesive in their groups. Instead, there are still students who do not want to cooperate and only rely on their friends to complete the tasks given by the teacher, resulting in a lot of wasted time. The author's objective in this study is to determine how the NHT cooperative strategy is implemented in Islamic Religious Education classes. This study uses descriptive qualitative field research. The data sources in this study were Islamic Religious Education teachers who were key informants, while the supporting informants were students of class XI office automation technology (OTP) and the curriculum representative of SMKN 1 Padang Panjang. The type of research used is descriptive qualitative field research. The data sources in this study are Islamic Education teachers who are key informants, while the supporting informants are grade XI Office Automation Technology (OTP) students and the curriculum representative of SMKN 1 Padang Panjang. The results of the study show that the number heads together (NHT) cooperative strategy in Islamic Religious Education on the material of principles and practices of economics in Islam can be understood through how a teacher implements the number heads together (NHT) cooperative strategy by applying the steps in the strategy used in the specified material, namely the material on the principles and practices of economics in Islam. Teachers also instill the values contained in the material to the students they teach so that the students can apply them in their daily lives.